Do as We Wish: Parental Tactics of Mate Choice Manipulation. (1st October 2013) - Apostolou, Menelaos
The mate choices of children do not always meet with the approval of their parents. As a consequence, the latter employ a battery of tactics that they use to manipulate the mating behavior of the former. This paper offers the first taxonomy of parental tactics of mate choice manipulation. In particular, in Study 1, 57 semi-structured interviews revealed 72 acts that parents employ to influence their children, and 27 that they employ to influence their children's partners. In Study 2, 405 parents rated how likely they were to use these acts to influence their daughters' and sons' mate choices. Factor analysis of participants' responses revealed 12 manipulation tactics that parents use on their children, and four manipulation tactics that they use on their children's partners.